Analysis of Fulfillment of Patient Legal Protection, Doctor Accountability, and Supervision Mechanisms for the Risk of Misdiagnosis in Digital Health Consultation - Nurhefi, Nurhefi; Vitrianingsih, Yeni; Issalillah, Fayola (Journal of Social Science Studies, 2023)
Advances in information technology have changed the pattern of interaction between patients and medical personnel through online health consultation services based on telemedicine. This study examines legal protection for patients who suffer losses due to misdiagnosis on digital platforms, the legal responsibility of doctors to provide online medical services, and the position of regulators and professional organisations in the supervisory system. The study was conducted through a normative approach and empirical studies that highlight the relevance of regulations, the effectiveness of ethical standards, and the readiness of supervision to ensure patient safety. The findings show that legal protection for patients is closely correlated with the certainty of standard procedures, the legality of medical personnel, and the security of personal data. Doctors are required to adhere to the principle of prudence, maintain professional communication, and ensure transparency before, during, and after digital consultation practices. Meanwhile, platform providers need to implement digital security policies and collaborate closely with health authorities and professional organisations. The government, together with health worker associations, plays an active role in developing an integrated supervisory system, drafting legal instruments, and providing continuous education. Research confirms the urgency of updating telemedicine regulations and strengthening the monitoring ecosystem for all stages of digital services. With cross-sector synergy, online health services can achieve better quality standards that are fair, safety-oriented, and ensure the rights of all users.